The Simple Beauty of the Unexpected : A Natural Philosopher's Quest for Trout and the Meaning of Everything - Gleiser, Marcelo (Book collections on Project MUSE., 2022)
"Personal and engaging, The Simple Beauty of the Unexpected is a scientist's tribute to nature, an affirmation of humanity's deep connection with and debt to Earth, and an exploration of the meaning of existence, from atom to trout to cosmos"--